Sperm proteins in teleostean and chondrostean (sturgeon) fishes - Li, Ping; Hulak, Martin; Linhart, Otomar (Fish physiology and biochemistry, 2009)
Sperm proteins in the seminal plasma and spermatozoa of teleostean and chondrostean have evolved adaptations due to the changes in the reproductive environment. Analysis of the composition and functions of these proteins provides new insights into sperm motility and fertilising abilities, thereby creating possibilities for improving artificial reproduction and germplasm resource conservation technologies (e.g. cryopreservation). Seminal plasma proteins are involved in the protection of spermatozoa during storage in the reproductive system, whereas all spermatozoa proteins contribute to the swimming and fertilising abilities of sperm. Compared to mammalian species, little data are available on fish sperm proteins and their functions. We review here the current state of the art in this field and focus on relevant subjects that require attention. Future research should concentrate on protein functions and their mode of action in fish species, especially on the role of spermatozoa surface proteins during fertilisation and on a description of sturgeon sperm proteins.
Keywords: Cryopreservation; Sperm Motility; spermie; mužské pohlaví; motilita spermií; Fishes; Proteins; zvířata; Semen; ryby; sperma; Spermatozoa; Male; Fertility; fertilita; kryoprezervace; proteiny; Animals